2020
DOI: 10.3389/fpsyt.2020.568717
|View full text |Cite
|
Sign up to set email alerts
|

State-Independent and -Dependent Structural Connectivity Alterations in Depression

Abstract: Some brain abnormalities persist at the remission phase, that is, the state-independent abnormalities, which may be one of the reasons for the high recurrence of major depressive disorder (MDD). Hence, it is of great significance to identify state-independent abnormalities of MDD through longitudinal investigation. Ninety-nine MDD patients and 118 healthy controls (HCs) received diffusion tensor imaging scanning at baseline. After 6-month antidepressant treatment, 68 patients received a second scan, among whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 51 publications
0
6
1
Order By: Relevance
“… Structural (cont.) Fan et al [ 35 ] 59 MDD, 118 HC -Paroxetine (SSRI) -6 months -FA -MRI before and after treatment Decreased SC between the right ATC and the posterior temporal cortex (PTC), and between the left temporal cortex and the auditory cortex were reversed at remission. Grieve et al [ 27 ] -74 MDD to calculate FA measures -83 MDD for replication -Escitalopram (SSRI), Sertraline (SSRI), or Venlafaxine-XR (SNRI) -8 weeks -FA of stria terminalis and cingulate bundle The ratio of the FA of the stria terminalis over the cingulate identified non-remitters with an accuracy of 83-88%, with greater specificity for Escitalopram and Sertraline.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… Structural (cont.) Fan et al [ 35 ] 59 MDD, 118 HC -Paroxetine (SSRI) -6 months -FA -MRI before and after treatment Decreased SC between the right ATC and the posterior temporal cortex (PTC), and between the left temporal cortex and the auditory cortex were reversed at remission. Grieve et al [ 27 ] -74 MDD to calculate FA measures -83 MDD for replication -Escitalopram (SSRI), Sertraline (SSRI), or Venlafaxine-XR (SNRI) -8 weeks -FA of stria terminalis and cingulate bundle The ratio of the FA of the stria terminalis over the cingulate identified non-remitters with an accuracy of 83-88%, with greater specificity for Escitalopram and Sertraline.…”
Section: Resultsmentioning
confidence: 99%
“…Fan et al (2020) found four SC alterations in patients with MDD compared to HC. After 6 months of Paroxetine, two of these alterations, between the right anterior and posterior temporal cortex, and between the left temporal cortex and the auditory cortex, reversed at remission, hinting towards state-dependent alterations in MDD [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…Tigecycline is an important antibiotic which can be used as a "last line of defense" against serious infections caused by multidrug-resistant (MDR) Gram-negative bacteria (Doan et al, 2006) which was launched for clinical usage in 2010 in China. Since then, it has been used increasingly in treating multidrug-resistant bacterial infections (Zhang et al, 2020a). However, owing to the increased use of tigecycline, including for treatment of carbapenem-resistant Enterobacteriaceae infections, tigecycline-resistant bacteria have emerged and now pose an important clinical concern (Kaewpoowat and Ostrosky-Zeichner, 2014;Ni et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The wide transmission of plasmid-mediated tet(X) in recent years presents a threat for clinical treatment of infections (Zhai et al, 2022), mutation of tet(X) into different variants has been observed with extended spectrum of activity of some conferring resistance to tigecycline (Yaghoubi et al, 2022). Among the different subtypes of tet(X), tet(X3)/tet(X4)/tet(X5) can mediate high-level resistance to tigecycline which is a clinical problem (Zhang et al, 2020a). Of these, tet(X4) has recently been detected from food-producing animals and is the most prevalent tet(X) subtype in China Feng et al, 2022;Wu et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation